Success by design: A holistic analysis of design principles for depression apps - Oliver Werth; Irene Jankowski; Nina S Müller; Fenja Schulte; Paula Warnemünde-Jagau; Michael H Breitner; Annika Herr; Kai G Kahl (Digital Health)
Objective Depression is a major challenge for many people and societies, also accelerated by the COVID-19 pandemic. Around 300 million people worldwide are affected by a depressive disorder. Health insurances encourage patients to use applications (“apps”) to tackle, for example, mild and moderate depression. The advantages of these depression apps are well understood, but their dissemination and adoption rates among intended users leave room for improvement. To enhance their uptake, we provide a holistic view regarding critical design aspects of depression apps and develop design principles (DPs) for depression apps. Methods We use a qualitative approach with 58 semistructured interviews between March 2021 and August 2022 with different stakeholders (healthcare providers, patients with mild and moderate depression, app developers and operators, and health insurance companies) to derive our DPs to provide a holistic view of the crucial design factors of depression apps. We then evaluated our DPs derived from four individuals from the health sector in terms of appropriateness and completeness. Results Following this approach, we examine seven meta-requirements (MRs) like “quality” and “simplicity” to deduce 16 corresponding DPs for depression apps. Our prescriptive design knowledge enables us to carve out interrelations and contributes to the literature on depression app design knowledge. Generally, our MRs and DPs derived were evaluated positively. Conclusions Our research ignites a structured discussion among stakeholders in the healthcare sector, for example, scientists and practitioners, about the importance of specific design aspects of depression apps and the overall development process from planning to dissemination.